2016
DOI: 10.5966/sctm.2015-0241
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Effect of Pediatric Cardiac Progenitor Cells After Juvenile Heart Failure

Abstract: To investigate the role of age of human pediatric cardiac progenitor cells (hCPCs) on ventricular remodeling, the authors injected neonate, infant, or child hCPCs into rats with right ventricular heart failure. Mechanisms including migration and proliferation assays, as suggested by computational modeling, showed improved chemotactic and proliferative capacity of neonatal hCPCs compared with infant or child hCPCs. Thus, the reparative potential of hCPCs is age-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 28 publications
4
72
0
Order By: Relevance
“…Our results also demonstrate that hypoxia reverses the phenotype of infant and child CPC-derived exosomes as we observed improved remodeling via increased angiogenesis and decreased fibrosis, suggesting another therapeutic approach in increasing the quality of these exosomes. As our recent study showed donor age-dependent effect of cells in response to right ventricular overload repair 15 , it is possible that hypoxia could alter the reparative phenotype of these cells as well.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Our results also demonstrate that hypoxia reverses the phenotype of infant and child CPC-derived exosomes as we observed improved remodeling via increased angiogenesis and decreased fibrosis, suggesting another therapeutic approach in increasing the quality of these exosomes. As our recent study showed donor age-dependent effect of cells in response to right ventricular overload repair 15 , it is possible that hypoxia could alter the reparative phenotype of these cells as well.…”
Section: Discussionmentioning
confidence: 98%
“…Approximately 70–100 mg of right atrial appendage tissue was obtained from children with varied congenital heart diseases, undergoing reconstructive heart surgeries. Human c-kit positive CPCs were isolated and characterized as described previously 15 . In brief, right atrial appendages of the children undergoing cardiac surgeries for various reasons were isolated and transported using Krebs-Ringer solution containing 35 mmol/L NaCl, 4.75 mmol/L KCl, 1.2 mmol/L KH 2 PO 4 , 16 mmol/L Na 2 HPO 4 , 134 mmol/L sucrose, 25 mmol/L NaHCO 3 , 10 mmol/L glucose, 10 mmol/L HEPES, and 30 mmol/L 2,3butanedionemonoxime, pH7.4, with NaOH.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, we have characterized the electrically induced Ca 2+ signal in CPCs by measuring the amplitude of cytosolic and nuclear Ca 2+ oscillations elicited by electrical stimulation, identified the mechanism by which Ca 2+ oscillations initiate and propagate throughout the cells, and also determined the key proteins involved in this process. Since our experiments were done in human pediatric CPCs, our results may be specific to that population of cells, and further experiments will be necessary to determine whether our results are species- or age-dependent [37]. To our knowledge, this is the first study to have reported the functional effect of acute ex vivo electrical stimulation on human CPCs.…”
Section: Discussionmentioning
confidence: 99%